Polyimide composite material and preparation method and application thereof
By blending and compositeing nanomaterials with polyimides to form polyimide composites, the existing polyimides have solved the problem of low thermal conductivity, and the combination of high thermal conductivity and high tensile strength is achieved. It is suitable for high temperature environments and a variety of industrial applications.
Patent Information
- Application Number
- CN202411864980.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-08
AI Technical Summary
The existing polyimide has low thermal conductivity and is difficult to meet the heat dissipation needs in high-temperature working environments.
By blending nanomaterials such as nanosilicon carbide, aluminum nitride, carbon nanotubes, graphene and nanosilicon dioxide with polyimide, polyimide composite materials are formed to improve their thermal conductivity.
It significantly improves the thermal conductivity of polyimide composite materials, enhances its heat dissipation ability in high temperature environments, and maintains high tensile strength, extends the service life of the material, and expands its application range.
Smart Images

Figure CN119777025A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of polymer materials, and in particular relates to a polyimide composite material and a preparation method and application thereof. Background Art
[0002] Polyimide fiber, also known as aromatic imide fiber, refers to the fiber containing aromatic imide in the molecular chain. Polyimide fiber is one of the organic synthetic fibers with the highest temperature resistance at present. It can be used as a flame retardant material to replace aramid in industrial scenarios. Polyimide fiber is superior to aramid and polyphenylene sulfide fiber in terms of light resistance, water absorption, and heat resistance. With excellent heat resistance and mechanical properties, polyimide fiber has a wide range of applications in high-performance chemical fibers with promising prospects in aerospace, military defense, digital electronics, new energy and other fields, and is considered to be the most promising in the 21st century.
[0003] Although the thermal conductivity of polyimide is usually in the range of 0.4W / (m·K)-0.8W / (m·K), its thermal conductivity is superior to other common polymer materials such as polyethylene and polystyrene. However, the molecular structure of polyimide is relatively dense, which makes heat transfer difficult. Therefore, the thermal conductivity of existing polyimide still needs to be improved. Summary of the invention
[0004] The purpose of the present application is to provide a polyimide composite material and a preparation method and application thereof, aiming to solve the problem that the thermal conductivity of existing polyimides needs to be improved to a certain extent.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect, the present application provides a method for preparing a polyimide composite material, comprising the following steps:
[0007] Prepare polyamic acid slurry by using diamine monomer, dianhydride monomer and organic solvent;
[0008] After the polyamic acid slurry and the nanomaterial are made into a mixed slurry, a spinning imidization treatment is performed to obtain a polyimide composite material; wherein the nanomaterial includes at least one of nano silicon carbide, aluminum nitride, carbon nanotube, graphene, and nano silicon dioxide.
[0009] In a second aspect, the present application provides a polyimide composite material, which includes polyimide and nanomaterials, wherein the nanomaterials include at least one of nano silicon carbide, aluminum nitride, carbon nanotubes, graphene, and nano silicon dioxide.
[0010] In a third aspect, the present application provides an application of a polyimide composite material, wherein the polyimide composite material or the polyimide composite material prepared by the above method is applied to at least one field of aerospace, electronics industry, automobile industry, protective products, and shipbuilding.
[0011] The preparation method of the polyimide composite material provided in the first aspect of the present application, while the diamine monomer and the dianhydride monomer are polymerized to generate the polyimide material, the nano material is in situ combined into the polyimide material to obtain the polyimide composite material. The nano materials such as nano silicon carbide, aluminum nitride, carbon nanotube, graphene, nano silicon dioxide and the like combined in situ have a higher thermal conductivity, and their thermal conductivity is higher than that of polyimide. In addition, these nano materials have good compatibility with polyimide. Among them, carbon nanotube and graphene can make the polyimide composite material have a certain electrical conductivity, and make the appearance color of the polyimide composite material black, and also can improve the heat resistance and mechanical properties of the polyimide composite material to a certain extent. The thermal conductivity of nano materials such as silicon carbide, aluminum nitride, nano silicon dioxide is lower than that of the first two, but the cost is lower, and the appearance color of the polyimide composite material will not approach black. By blending polyimide with other nanomaterials with high thermal conductivity to improve its thermal conductivity, the thermal conductivity of polyimide composite materials is optimized and improved, and its heat dissipation capacity in high-temperature working environments is enhanced, while having high tensile strength and thermal conductivity. The service life of polyimide composite materials can be extended, and their application range can be further expanded, such as in the back panel components of smartphones.
[0012] The polyimide composite material provided in the second aspect of the present application includes polyimide and nanomaterials, wherein the nanomaterial includes at least one of nano silicon carbide (SiC), aluminum nitride (AlN), carbon nanotubes, graphene, and nano silicon dioxide (SiO2), and these nanomaterials have higher thermal conductivity, and their thermal conductivity is higher than that of polyimide. In addition, these nanomaterials have good compatibility with polyimide. By blending polyimide with other nanomaterials with high thermal conductivity to improve its thermal conductivity, the thermal conductivity of the polyimide composite material is optimized and improved, and its heat dissipation capacity in a high temperature working environment is enhanced. The polyimide composite material has stronger thermal conductivity while having high tensile strength. Extend the service life of the polyimide composite material, and at the same time, its application range can be further expanded, such as being applied to the back panel assembly of a smartphone.
[0013] The above-mentioned polyimide composite material of the present application has both high tensile strength and thermal conductivity, and can be widely used in aerospace, electronics industry, automobile industry, protective products, shipbuilding and other fields, with a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0015] Figure 1 It is a schematic diagram of the process of preparing the polyimide composite material provided in the embodiment of the present application. DETAILED DESCRIPTION
[0016] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0017] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0018] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0019] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0020] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0021] The weight of the relevant components mentioned in the embodiments of the present specification can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present specification. Specifically, the mass described in the embodiments of the present specification can be μg, mg, g, kg and other mass units known in the chemical industry.
[0022] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0023] In a first aspect, the present invention provides a method for preparing a polyimide composite material, as shown in the attached Figure 1 As shown, the following steps are included:
[0024] S10. The diamine monomer, the dianhydride monomer and the organic solvent are prepared into a polyamic acid slurry;
[0025] S20. After preparing a mixed slurry of polyamic acid slurry and nanomaterials, the mixed slurry is subjected to spinning imidization treatment to obtain a polyimide composite material; wherein the nanomaterial includes at least one of nano silicon carbide, aluminum nitride, carbon nanotubes, graphene, and nano silicon dioxide.
[0026] The preparation method of the polyimide composite material of the embodiment of the present application, while the diamine monomer and the dianhydride monomer are polymerized to generate the polyimide material, the nano material is in situ combined into the polyimide material to obtain the polyimide composite material. The nano materials such as nano silicon carbide, aluminum nitride, carbon nanotube, graphene, nano silicon dioxide and the like combined in situ have a higher thermal conductivity, and their thermal conductivity is higher than that of polyimide. In addition, there is good compatibility between these nano materials and polyimide. Among them, carbon nanotube and graphene can make the polyimide composite material have a certain electrical conductivity, and make the appearance color of the polyimide composite material black, and also can improve the heat resistance and mechanical properties of the polyimide composite material to a certain extent. The thermal conductivity of nano materials such as silicon carbide, aluminum nitride, nano silicon dioxide is lower than that of the first two, but the cost is lower, and the appearance color of the polyimide composite material will not approach black. By blending polyimide with other nanomaterials with high thermal conductivity to improve its thermal conductivity, the thermal conductivity of polyimide composite materials is optimized and improved, and its heat dissipation capacity in high-temperature working environments is enhanced, while having high tensile strength and thermal conductivity. The service life of polyimide composite materials can be extended, and their application range can be further expanded, such as in the back panel components of smartphones.
[0027] In the above step S10:
[0028] In some possible implementations, the diamine monomer includes at least one of 4,4'-diaminodiphenyl ether (ODA), p-phenylenediamine (p-PDA), m-phenylenediamine (m-PDA), 4,4'-diaminobenzanilide (DABA), 2-(4-aminophenyl)-5-aminobenzimidazole (R3), and 2-(4-aminophenyl)-5-aminobenzoxazole (APBOA). These diamine monomers can be polymerized with dianhydride monomers to generate polyimide materials.
[0029] In some embodiments, the diamine monomer includes at least two of 4,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminobenzanilide, 2-(4-aminophenyl)-5-aminobenzimidazole, and 2-(4-aminophenyl)-5-aminobenzoxazole. In this case, the polyimide material is prepared by two diamine monomers to form hydrogen bonds between polymer chains, which can better provide the tensile strength of the polyimide composite material. At the same time, by mixing high thermal conductivity nanomaterials, the high-strength polyimide composite material has a high thermal conductivity, which not only improves the tensile strength of the polyimide composite material, but also improves the thermal conductivity of the polyimide composite material, so that its application range is further expanded, which is of great significance to the field of high-performance polyimide composite materials.
[0030] In some possible implementations, the dianhydride monomer includes at least one of pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), 4,4'-biphenyl ether dianhydride (ODPA), and bisphenol A diether dianhydride (BPADA). These dianhydride monomers can be polymerized with diamine monomers to generate polyimide materials.
[0031] In some possible implementations, the molar ratio of the diamine monomer to the dianhydride monomer is (0.95-1.05): 1. Exemplarily, the molar ratio of the diamine monomer to the dianhydride monomer can be 0.95:1, 0.96:1, 0.97:1, 0.98:1, 0.99:1, 1.0:1, 1.05:1, and other typical but non-restrictive arbitrary point values or interval values between any two point values. In this case, considering the viscosity of the polyamic acid, the viscosity of the polyamic acid slurry can be effectively controlled by adjusting the molar ratio between the two types of monomers, diamine and dianhydride, so that it is convenient to produce polyimide composite fibers through processes such as spinning. Generally, when the molar ratio between the two monomers is within ±5%, a polyamic acid slurry with suitable viscosity can be obtained to ensure the performance of the polyimide composite material. Otherwise, the slurry viscosity will be too low or too high, which is not conducive to the industrial preparation of polyimide.
[0032] In some possible implementations, the organic solvent includes at least one of N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), γ-butyrolactone (GBL), and cyclohexanone (CHO); these organic solvents have a good dissolving effect on diamine monomers and dianhydride monomers, which is beneficial to the polymerization of diamine monomers and dianhydride monomers to form polyamic acid slurry.
[0033] In some possible implementations, the preparation steps of the polyamic acid slurry include: dissolving the diamine monomer in an organic solvent under an inert atmosphere at a temperature of 40°C to 50°C, and adding the dianhydride monomer after cooling to 0°C to 5°C for mixing. In this case, the diamine monomer is added at a higher temperature to make the diamine monomer dispersed evenly in the solvent and improve the uniformity of the diamine monomer dispersion. In addition, the addition of dianhydride at a lower temperature is to increase the polymerization reaction limit. The reaction of the diamine monomer and the dianhydride monomer to obtain polyamic acid is a reversible reaction. The equilibrium of the reversible reaction is significantly affected by temperature. Too high a temperature will cause the reaction equilibrium to move in the direction of breaking the polyamic acid molecular chain and decreasing the degree of polymerization, resulting in too low a molecular weight and too low a viscosity to obtain a qualified polyamic acid slurry.
[0034] In some embodiments, the temperature is 40°C to 50°C in an inert atmosphere, which may be nitrogen, argon, helium, etc. The temperature may be any typical but non-limiting point value such as 40°C, 45°C, 50°C, or an interval value between any two points.
[0035] In some embodiments, the cooling temperature may be any typical but non-limiting point value such as 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, or an interval value between any two points.
[0036] In some embodiments, the mixing processing duration may be any typical but non-limiting point value such as 10 h, 12 h, 15 h, 18 h, 20 h, 24 h, or an interval value between any two point values.
[0037] In some possible implementations, the viscosity of the polyamic acid slurry is 30000cps to 300000cps. Exemplarily, the viscosity of the polyamic acid slurry can be 30000cps, 50000cps, 80000cps, 100000cps, 150000cps, 200000cps, 250000cps, 300000cps, and other typical but non-limiting arbitrary point values or interval values between any two point values. When the viscosity of the polyamic acid slurry is lower than this viscosity range, the dianhydride monomer can be added in batches to increase its viscosity. When the viscosity of the polyamic acid slurry is higher than this viscosity range, it can be diluted by adding a solvent to reduce its viscosity. The added solvent can be the same solvent used for the polymerization reaction, or it can be other solvents. The production equipment and process of polyimide composite materials have certain requirements for the viscosity of polyamic acid slurry. Controlling the viscosity of polyamic acid within this range is more conducive to the production of polyimide composite products. When the viscosity is too low, the polyamic acid slurry is difficult to form into polyamic acid fibers. When the viscosity is too high, it will affect the spinning process and cause damage to the spinneret, etc.
[0038] In the above step S20: after the polyamic acid slurry and the nanomaterial are made into a mixed slurry, a spinning imidization treatment is performed, and the mixed slurry is ejected from the spinneret to form primary fibers in a coagulation bath, and then enters a high-temperature drying tunnel after washing and drying. Under tension stretching, the polyamic acid is dehydrated and closed-looped through thermal imidization to form polyimide fibers with a certain tensile strength, and the nanomaterial is in-situ combined with the polyimide fiber to obtain a polyimide composite fiber.
[0039] In some embodiments, in the nanomaterials in situ combined in the polyimide composite material, the particle size D50 of particles such as silicon carbide, aluminum nitride, and nano silicon dioxide is preferably between 10nm and 50nm. If the particle size is too large, it will affect the adhesion between the polyimide molecular chains and the hydrogen bonds between the polyimide molecular chains. If the particle size is too small, the particles are more likely to agglomerate and affect their compatibility with the polyimide composite material. For carbon nanotubes, the tube length is preferably smaller than the spinneret caliber and filter element pore size of the spinning process to avoid clogging; for multilayer graphene oxide, the sheet diameter is also preferably smaller than the spinneret caliber and filter element pore size of the spinning process to avoid clogging. Exemplarily, in nanomaterials, the particle size can be 10nm, 20nm, 30nm, 40nm, 50nm, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0040] In some embodiments, the carbon nanotubes are selected from silsesquioxane-grafted multi-walled carbon nanotubes; that is, silsesquioxane molecules are grafted onto the surface of multi-walled carbon nanotubes. Multi-walled carbon nanotubes are one-dimensional quantum materials formed by multiple layers of graphene layers curled around the central axis at a certain spiral angle, and have excellent properties such as high strength, high toughness, high electrical conductivity and high thermal conductivity. Silsesquioxane is a class of organic silicon compounds with special structures and properties. Through specific chemical reactions, it can be grafted onto the surface of multi-walled carbon nanotubes, thereby giving carbon nanotubes new properties and applications. After silsesquioxane grafting, the dispersibility and compatibility of multi-walled carbon nanotubes in the polymer matrix can be improved, and the interface interaction between carbon nanotubes and the polymer matrix can be enhanced, thereby improving the overall performance of the composite material. Multi-walled carbon nanotubes themselves have high thermal conductivity. After silsesquioxane grafting, their thermal conductivity path in the polymer can be further optimized, thereby improving the thermal conductivity of the composite material. Silsesquioxane-grafted multi-walled carbon nanotubes can be used as a reinforcing agent to significantly improve the mechanical properties of the composite material such as tensile strength and elastic modulus. In the polyimide matrix, silsesquioxane grafted multi-walled carbon nanotubes have significantly promoted the thermal conductivity and tensile strength of polyimide materials by forming thermal conduction paths, improving thermal conductivity, enhancing interface interactions, and acting as a reinforcing agent. These performance improvements make polyimide materials have a wider application prospect in high-tech fields such as electronics, aerospace, and automobiles.
[0041] In certain embodiments, graphene is selected from multilayer graphene oxide. In this case, multilayer graphene oxide, as a high-strength, high-modulus nanomaterial, can be used as a reinforcing agent for polyimide. When they are evenly dispersed in a polyimide matrix, the tensile strength of the composite material can be effectively improved. The functional groups on the surface of multilayer graphene oxide can interact with the polyimide molecular chain, such as hydrogen bonding, etc. This interaction helps to enhance the interfacial bonding force between multilayer graphene oxide and the polyimide matrix, thereby further improving the tensile strength of the composite material. In addition, multilayer graphene oxide has extremely high thermal conductivity, and can form effective heat conduction paths in the polyimide matrix, and these paths contribute to the rapid transfer of heat. The interfacial interaction between multilayer graphene oxide and the polyimide matrix is enhanced, which helps to reduce thermal interface resistance.
[0042] In some possible implementations, the mass of the nanomaterial is 0.1% to 2% of the total mass of the diamine monomer and the dianhydride monomer. Exemplarily, the mass of the nanomaterial is 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2% of the total mass of the diamine monomer and the dianhydride monomer, and other typical but non-restrictive arbitrary point values or interval values between any two point values. In this case, the amount of nanomaterial added can fully ensure that the tensile strength and thermal conductivity of the finished polyimide composite material are significantly improved, and the stability of the polyimide composite material is ensured. Avoid excessive agglomeration of nanomaterials and precipitation and falling from the surface of polyimide.
[0043] In some possible implementations, the step of spinning imidization treatment includes: the mixed slurry is extruded through spinning metering at a spinning speed of 15 m / min to 25 m / min according to a linear density specification of 1000 dtex to 2000 dtex, and the polyamic acid undergoes a dehydration ring-closing reaction at a temperature of 400°C to 600°C to obtain a polyimide composite fiber. The reaction of converting polyamic acid into polyimide in the embodiment of the present application is completed simultaneously under the high temperature conditions of the spinning process. The polyamic acid undergoes a dehydration ring-closing reaction under the high temperature conditions of spinning (usually a temperature above 400°C), so that the polyamic acid fiber is converted into a polyimide composite material.
[0044] Exemplarily, the linear density of the imidization treatment can be 1000dtex, 1200dtex, 1500dtex, 1800dtex, 2000dtex, etc., typical but non-limiting arbitrary point values or interval values between any two point values; the spinning speed can be 15m / min, 18m / min, 20m / min, 21m / min, 23m / min, 25m / min, etc., typical but non-limiting arbitrary point values or interval values between any two point values; the temperature can be 400°C, 450°C, 500°C, 550°C, 600°C, etc., typical but non-limiting arbitrary point values or interval values between any two point values.
[0045] In some possible implementations, the nanomaterial includes silsesquioxane-grafted multi-walled carbon nanotubes, and its preparation includes the steps of: dispersing carboxylated multi-walled carbon nanotubes in a thionyl chloride solvent under an inert atmosphere, and refluxing to obtain acyl chloride multi-walled carbon nanotubes; dispersing acyl chloride multi-walled carbon nanotubes, triethylamine, and aminated silsesquioxane in chloroform for mixed reaction, and separating and purifying the reaction product to obtain silsesquioxane-grafted multi-walled carbon nanotubes.
[0046] In some possible implementations, the mass ratio of chlorinated multi-walled carbon nanotubes, triethylamine and amination of silsesquioxane is 1:(0.8-1.2):(1.8-2.5); under this ratio, it is more conducive to preparing silsesquioxane-grafted multi-walled carbon nanotubes. Exemplarily, the mass ratio of chlorinated multi-walled carbon nanotubes, triethylamine and amination of silsesquioxane can be 1:1:2, 1:0.8:1.8, 1:1.2:2.5, and other typical but non-limiting arbitrary point values or interval values between any two point values.
[0047] In some possible implementations, the temperature of the mixed reaction is 60°C to 70°C, and the treatment time is 12 to 36 hours. In this case, it can be fully ensured that the reaction proceeds in the forward direction to obtain silsesquioxane-grafted multi-walled carbon nanotubes. Exemplarily, the temperature of the mixed reaction can be 60°C, 65°C, 68°C, 70°C, etc., typical but non-limiting arbitrary point values or interval values between any two point values, and the duration can be 12 hours, 18 hours, 24 hours, 36 hours, etc., typical but non-limiting arbitrary point values or interval values between any two point values.
[0048] In some embodiments, the preparation of silsesquioxane grafted multi-walled carbon nanotubes includes the following steps: under nitrogen protection, adding 40 to 60 g of carboxylated multi-walled carbon nanotube (MWCNTs) powder into a three-necked flask, adding 400 to 500 g of thionyl chloride (SOCl2) into the three-necked flask, placing the three-necked flask in an ultrasonic bath, and continuously ultrasonically oscillating at a power of 40 to 80 W for 3 hours to uniformly disperse the MWCNTs; continuously refluxing the reaction solution at 70 to 80° C. for 12 hours; and removing SOCl2 from the reaction solution by reduced pressure distillation to obtain acyl chloride multi-walled carbon nanotubes (MWTNCs-COCl). Under nitrogen protection, the obtained MWTNCs-COCl was placed in a three-necked flask, triethylamine (TEA) was added, wherein the mass ratio of TEA to MWTNCs-COCl was 1: (0.8-1.2), the purchased amino silsesquioxane (POSS-NH2) was added, wherein the mass ratio of POSS-NH2 to MWTNCs-COCl was (1.8-2.5): 1, and chloroform twice the mass of MWTNCs-COCl was added, and ultrasonic vibration was continuously performed at a power of 40-80 W. Swing for 1 to 5 hours to disperse evenly; put the three-necked flask in a 60-70° C. water bath and continue stirring for 12 to 36 hours to obtain an insoluble product; filter, wash and dry the reaction product to obtain pure silsesquioxane grafted multi-walled carbon nanotubes (POSS-MWCNTs); disperse the above POSS-MWCNTs in NMP solvent at a power of 100 to 150 W, continue ultrasonic oscillation for 1 to 3 hours to obtain a POSS-MWCNTs solution with a solid content of 5 to 20%, and set aside.
[0049] In a second aspect, an embodiment of the present application provides a polyimide composite material, which includes polyimide and nanomaterials, wherein the nanomaterials include at least one of nano silicon carbide (SiC), aluminum nitride (AlN), carbon nanotubes, graphene, and nano silicon dioxide (SiO2).
[0050] The polyimide composite material provided in the first aspect of the embodiment of the present application includes polyimide and nanomaterials, wherein the nanomaterials include at least one of nano silicon carbide (SiC), aluminum nitride (AlN), carbon nanotubes, graphene, and nano silicon dioxide (SiO2), and these nanomaterials have higher thermal conductivity, and their thermal conductivity is higher than that of polyimide. In addition, these nanomaterials have good compatibility with polyimide. By blending polyimide with other nanomaterials with high thermal conductivity to improve its thermal conductivity, the thermal conductivity of the polyimide composite material is optimized and improved, and its heat dissipation capacity in a high temperature working environment is enhanced. The polyimide composite material has a stronger thermal conductivity while having high tensile strength. Extend the service life of the polyimide composite material, and at the same time, its application range can be further expanded, such as being applied to the back panel components of smart phones.
[0051] In some embodiments, among the nanomaterials in situ combined in the polyimide composite material, the particle size D50 of silicon carbide, aluminum nitride, nano silicon dioxide and the like is preferably between 10nm and 50nm. If the particle size is too large, it will affect the adhesion between the particles and the polyimide molecular chains, and will affect the hydrogen bonds between the polyimide molecular chains. If the particle size is too small, the particles are more likely to agglomerate, affecting their compatibility with the polyimide composite material. For carbon nanotubes, the tube length is preferably smaller than the spinneret caliber and filter element pore diameter of the spinning process to avoid clogging; for multilayer graphene oxide, the sheet diameter is also preferably smaller than the spinneret caliber and filter element pore diameter of the spinning process to avoid clogging.
[0052] In some embodiments, the carbon nanotubes are selected from silsesquioxane-grafted multi-walled carbon nanotubes; that is, silsesquioxane molecules are grafted onto the surface of multi-walled carbon nanotubes. Multi-walled carbon nanotubes are one-dimensional quantum materials formed by multiple layers of graphene layers curled around the central axis at a certain spiral angle, and have excellent properties such as high strength, high toughness, high electrical conductivity and high thermal conductivity. Silsesquioxane is a class of organic silicon compounds with special structures and properties. Through specific chemical reactions, it can be grafted onto the surface of multi-walled carbon nanotubes, thereby giving carbon nanotubes new properties and applications. After silsesquioxane grafting, the dispersibility and compatibility of multi-walled carbon nanotubes in the polymer matrix can be improved, and the interface interaction between carbon nanotubes and the polymer matrix can be enhanced, thereby improving the overall performance of the composite material. Multi-walled carbon nanotubes themselves have high thermal conductivity. After silsesquioxane grafting, their thermal conductivity path in the polymer can be further optimized, thereby improving the thermal conductivity of the composite material. Silsesquioxane-grafted multi-walled carbon nanotubes can be used as a reinforcing agent to significantly improve the mechanical properties of the composite material such as tensile strength and elastic modulus. In the polyimide matrix, silsesquioxane grafted multi-walled carbon nanotubes have significantly promoted the thermal conductivity and tensile strength of polyimide materials by forming thermal conduction paths, improving thermal conductivity, enhancing interface interactions, and acting as a reinforcing agent. These performance improvements make polyimide materials have a wider application prospect in high-tech fields such as electronics, aerospace, and automobiles.
[0053] In certain embodiments, graphene is selected from multilayer graphene oxide. In this case, multilayer graphene oxide, as a high-strength, high-modulus nanomaterial, can be used as a reinforcing agent for polyimide. When they are evenly dispersed in a polyimide matrix, the tensile strength of the composite material can be effectively improved. The functional groups on the surface of multilayer graphene oxide can interact with the polyimide molecular chain, such as hydrogen bonding, etc. This interaction helps to enhance the interfacial bonding force between multilayer graphene oxide and the polyimide matrix, thereby further improving the tensile strength of the composite material. In addition, multilayer graphene oxide has extremely high thermal conductivity, and can form effective heat conduction paths in the polyimide matrix, and these paths contribute to the rapid transfer of heat. The interfacial interaction between multilayer graphene oxide and the polyimide matrix is enhanced, which helps to reduce thermal interface resistance.
[0054] In some possible implementations, the mass percentage of nanomaterials in the polyimide composite material is 0.1% to 2%. Exemplarily, the mass of the nanomaterial is 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2% of the total mass of the diamine monomer and the dianhydride monomer, and other typical but non-restrictive arbitrary point values or interval values between any two point values. In this case, the amount of nanomaterial added can fully ensure that the tensile strength and thermal conductivity of the finished polyimide composite material are significantly improved, and the stability of the polyimide composite material is ensured. Avoid excessive agglomeration of nanomaterials and precipitation and falling from the surface of polyimide.
[0055] In some possible implementations, the polyimide composite material is a polyimide composite fiber. In this case, the polyimide composite fiber is more convenient to use. The polyimide composite fiber has high thermal conductivity, strength and modulus, which enables it to replace traditional materials and meet the requirements of light weight and high strength. High strength means that the fiber can withstand greater tension and is not easy to break, thereby improving the durability and safety of the product.
[0056] In some possible implementations, the thermal conductivity of the polyimide composite material is not less than 0.93 W / (m·K); it has excellent thermal conductivity. Exemplarily, the thermal conductivity of the polyimide composite material can be 0.93 W / (m·K), 0.95 W / (m·K), 1.0 W / (m·K), 1.02 W / (m·K), 1.1 W / (m·K), 1.2 W / (m·K), 1.3 W / (m·K), 1.39 W / (m·K), 1.4 W / (m·K), 1.5 W / (m·K), 1.53 W / (m·K), 1.6 W / (m·K), 1.7 W / (m·K), 1.8 W / (m·K), 1.9 W / (m·K), 2 W / (m·K), and other typical but non-limiting arbitrary point values or interval values between any two point values.
[0057] In some possible implementations, the tensile strength of the polyimide composite material is not less than 25 cN / dtex, and has excellent tensile strength. Wherein, cN / dtex represents the centinewon (cN) force that each dtex fiber can withstand. Exemplarily, the tensile strength of the polyimide composite material can be 25 cN / dtex, 25.13 cN / dtex, 25.49 cN / dtex, 25.86 cN / dtex, 26 cN / dtex, 26.5 cN / dtex, 27 cN / dtex, 27.31 cN / dtex, 27.53 cN / dtex, 28 cN / dtex, 29 cN / dtex, 30 cN / dtex, etc., typical but non-restrictive arbitrary point values or interval values between any two point values.
[0058] In some possible implementations, the diameter of the polyimide composite fiber is 5 μm to 15 μm; under this diameter condition, it is more conducive to application. Exemplarily, the diameter of the polyimide composite fiber can be 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, etc., which are typical but non-limiting arbitrary point values or interval values between any two point values.
[0059] In some possible implementations, the linear density of the polyimide composite fiber is 1000 dtex to 2000 dtex. Within this linear density range, the polyimide composite fiber generally has higher strength and modulus, and can withstand greater external forces without breaking easily. Such high strength and high modulus properties give the fiber a significant advantage in the manufacture of high-performance materials, such as for the manufacture of high-strength ropes, composite materials, and the like. Among them, dtex is the unit of fiber linear density, which represents the weight (grams) of a 10,000-meter fiber bundle, and a linear density of 1000 dtex means that the total mass of a 10,000-meter-long bundle is 1000 g. Exemplarily, the linear density of the polyimide composite fiber can be 1000 dtex, 1200 dtex, 1500 dtex, 1800 dtex, 2000 dtex, and other typical but non-restrictive arbitrary point values or interval values between any two point values.
[0060] The polyimide composite material of the embodiment of the present application can be prepared by the method of the embodiment described above.
[0061] In a third aspect, an embodiment of the present application provides an application of a polyimide composite material, wherein the above-mentioned polyimide composite material, or the polyimide composite material prepared by the above-mentioned method is applied to at least one field of aerospace, electronics industry, automobile industry, protective products, and shipbuilding.
[0062] The polyimide composite material in the embodiment of the present application has both high tensile strength and thermal conductivity, and can be widely used in aerospace, electronics industry, automobile industry, protective products, shipbuilding and other fields, with a wide range of applications.
[0063] In order to enable those skilled in the art to clearly understand the implementation details and operations of the present application, and to demonstrate the significant improvement in the performance of the polyimide composite material and the preparation method thereof in the embodiments of the present application, the above technical solution is illustrated by multiple embodiments below.
[0064] Example 1
[0065] A polyimide composite fiber, the preparation of which comprises the following steps:
[0066] 1. Preparation of silsesquioxane grafted multi-walled carbon nanotube solution:
[0067] ① Under nitrogen protection, 50 g of purchased carboxylated multi-walled carbon nanotubes (MWCNTs) powder was added to a three-necked flask, 450 g of thionyl chloride (SOCl2) was added to the three-necked flask, the three-necked flask was placed in an ultrasonic bath, and ultrasonic vibration was continued at 60 W for 3 h to make the MWCNTs evenly dispersed; the above reaction solution was refluxed at 75 ° C for 12 h; SOCl2 in the above reaction solution was removed by vacuum distillation to obtain acyl chloride multi-walled carbon nanotubes (MWTNCs-COCl);
[0068] ② Under nitrogen protection, the MWTNCs-COCl obtained above was placed in a three-necked flask, triethylamine (TEA) was added, wherein the mass ratio of TEA to MWTNCs-COCl was 1:1, the purchased amino silsesquioxane (POSS-NH2) was added, wherein the mass ratio of POSS-NH2 to MWTNCs-COCl was 2:1, and chloroform twice the mass of MWTNCs-COCl was added, and ultrasonic vibration was continued at 60W power for 3h to disperse evenly; the three-necked flask was placed in a 65℃ water bath and stirred continuously for 24h to obtain an insoluble product; the reaction product was filtered, washed and dried to obtain pure silsesquioxane grafted multi-walled carbon nanotubes (POSS-MWCNTs);
[0069] ③ The POSS-MWCNTs were dispersed in NMP solvent at a power of 120 W and ultrasonically shaken for 2 h to obtain a POSS-MWCNTs solution with a solid content of 10%.
[0070] 2. Preparation of polyimide composite fibers:
[0071] ① Circulating water at a temperature of 45°C was introduced into the jacket of a 50L reactor into which nitrogen was continuously introduced to preheat the reactor; after the reactor was preheated, 40kg of NMP solvent was added into the reactor and heated in a water bath; a NMP sample was taken from the reactor using a vial for moisture test, and the test result was 128.531ppm; 1527.29g of diamine monomer R3 and 245.59g of diamine monomer p-PDA were weighed and all were put into the NMP solvent at one time, and stirred continuously in a warm water bath for 3h until uniformly dispersed; the warm water in the jacket of the reactor was discharged, and cooling water at a temperature of 5°C was filled in, and the solution with uniformly dispersed diamine monomers was cooled to 5°C; 2671.66g of dianhydride monomer BPDA was added to the cooled solution in the reactor; stirring was continued for 12h, and the dianhydride monomer and the diamine monomer were polymerized to form a polyamic acid slurry;
[0072] ② Take a sample to test the dynamic viscosity of the polyamic acid slurry, and the test result is 83541cps; add 444.44g of the POSS-MWCNTs solution prepared in step 1 above into the above polyamic acid slurry, and stir it for 3h to make the POSS-MWCNTs evenly dispersed in the polyamic acid slurry;
[0073] ③ The viscosity of the polyamic acid slurry sampled and tested was 77649 cps. The polyamic acid slurry with qualified viscosity was transferred to a storage tank for wet spinning. According to the 1500 dtex linear density specification, the slurry was extruded at a spinning speed of 20 m / min through spinning metering. The polyamic acid underwent a dehydration and ring-closing reaction at a temperature of 500°C to obtain a finished polyimide composite fiber.
[0074] Example 2
[0075] A polyimide composite fiber, the preparation of which comprises the following steps:
[0076] ① Circulating water at a temperature of 45°C was introduced into the jacket of a 50L reactor into which nitrogen was continuously introduced to preheat the reactor; after the reactor was preheated, 40kg of NMP solvent was added into the reactor and heated in a water bath; a NMP sample was taken from the reactor using a vial for moisture test, and the test result was 128.531ppm; 1527.29g of diamine monomer R3 and 245.59g of diamine monomer p-PDA were weighed and all were put into the NMP solvent at one time, and stirred continuously in a warm water bath for 3h until uniformly dispersed; the warm water in the jacket of the reactor was discharged, and cooling water at a temperature of 5°C was filled in to cool the solution in which the diamine monomer had been uniformly dispersed to 5°C; 2671.66g of dianhydride monomer BPDA was added to the cooled solution in the reactor; stirring was continued for 12h, and the dianhydride monomer and the diamine monomer were polymerized to form a polyamic acid slurry;
[0077] ② Take a sample to test the dynamic viscosity of the polyamic acid slurry, and the test result is 92769cps; add 444.44g of 10% mass fraction NMP dispersion of multilayer graphene oxide (sheet diameter 4-10μm) into the above polyamic acid slurry, stir well for 3h, so that the multilayer graphene oxide is evenly dispersed in the polyamic acid slurry;
[0078] ③ The viscosity of the polyamic acid slurry sampled and tested was 80211cps. The polyamic acid slurry with qualified viscosity was transferred to a storage tank for wet spinning. According to the 1500dtex linear density specification, the slurry was extruded at a spinning speed of 20m / min through spinning metering. The polyamic acid underwent a dehydration ring-closing reaction at a temperature of 500°C to obtain a finished polyimide composite fiber.
[0079] Example 3
[0080] A polyimide composite fiber, the preparation of which comprises the following steps:
[0081] ① Circulating water at a temperature of 45°C was introduced into the jacket of a 50L reactor into which nitrogen was continuously introduced to preheat the reactor; after the reactor was preheated, 40kg of NMP solvent was added into the reactor and heated in a water bath; a NMP sample was taken from the reactor using a vial for moisture test, and the test result was 128.531ppm; 1527.29g of diamine monomer R3 and 245.59g of diamine monomer p-PDA were weighed and all were put into the NMP solvent at one time, and stirred continuously in a warm water bath for 3h until uniformly dispersed; the warm water in the jacket of the reactor was discharged, and cooling water at a temperature of 5°C was filled in to cool the solution in which the diamine monomer had been uniformly dispersed to 5°C; 2671.66g of dianhydride monomer BPDA was added to the cooled solution in the reactor; stirring was continued for 12h, and the dianhydride monomer and the diamine monomer were polymerized to form a polyamic acid slurry;
[0082] ② Take a sample to test the dynamic viscosity of the polyamic acid slurry, and the test result is 88831cps; add 222.22g of 20% mass fraction NMP dispersion of nano-silicon dioxide (average particle size 30nm) into the above polyamic acid slurry, and stir it for 3h to make the nano-silicon dioxide evenly dispersed in the polyamic acid slurry;
[0083] ③ The viscosity of the polyamic acid slurry sampled and tested was 81004cps. The polyamic acid slurry with qualified viscosity was transferred to a storage tank for wet spinning. According to the 1500dtex linear density specification, it was extruded at a spinning speed of 20m / min through spinning metering. The polyamic acid underwent a dehydration ring-closing reaction at a temperature of 500°C to obtain a finished polyimide composite fiber.
[0084] Example 4
[0085] A polyimide composite fiber, the preparation of which comprises the following steps:
[0086] ① Circulating water at a temperature of 45°C was introduced into the jacket of a 50L reactor into which nitrogen was continuously introduced to preheat the reactor; after the reactor was preheated, 40kg of NMP solvent was added into the reactor and heated in a water bath; a NMP sample was taken from the reactor using a vial for moisture test, and the test result was 128.531ppm; 1527.29g of diamine monomer R3 and 245.59g of diamine monomer p-PDA were weighed and all were put into the NMP solvent at one time, and stirred continuously in a warm water bath for 3h until uniformly dispersed; the warm water in the jacket of the reactor was discharged, and cooling water at a temperature of 5°C was filled in to cool the solution in which the diamine monomer had been uniformly dispersed to 5°C; 2671.66g of dianhydride monomer BPDA was added to the cooled solution in the reactor; stirring was continued for 12h, and the dianhydride monomer and the diamine monomer were polymerized to form a polyamic acid slurry;
[0087] ② Take a sample to test the dynamic viscosity of the polyamic acid slurry, and the test result is 83145cps; add 444.44g of 10% mass fraction NMP dispersion of nano-silicon carbide (average particle size 30nm) into the above polyamic acid slurry, and stir it for 3h to make the nano-silicon carbide evenly dispersed in the polyamic acid slurry;
[0088] ③ The viscosity of the polyamic acid slurry sampled and tested was 74429 cps. The polyamic acid slurry with qualified viscosity was transferred to a storage tank for wet spinning. According to the 1500 dtex linear density specification, the slurry was extruded at a spinning speed of 20 m / min through spinning metering. The polyamic acid underwent a dehydration ring-closing reaction at a temperature of 500°C to obtain a finished polyimide composite fiber.
[0089] Example 5
[0090] A polyimide composite fiber, the preparation of which comprises the following steps:
[0091] ① Circulating water at a temperature of 45°C was introduced into the jacket of a 50L reactor into which nitrogen was continuously introduced to preheat the reactor; after the reactor was preheated, 40kg of NMP solvent was added into the reactor and heated in a water bath; a NMP sample was taken from the reactor using a vial for moisture test, and the test result was 128.531ppm; 1527.29g of diamine monomer R3 and 245.59g of diamine monomer p-PDA were weighed and all were put into the NMP solvent at one time, and stirred continuously in a warm water bath for 3h until uniformly dispersed; the warm water in the jacket of the reactor was discharged, and cooling water at a temperature of 5°C was filled in to cool the solution in which the diamine monomer had been uniformly dispersed to 5°C; 2671.66g of dianhydride monomer BPDA was added to the cooled solution in the reactor; stirring was continued for 12h, and the dianhydride monomer and the diamine monomer were polymerized to form a polyamic acid slurry;
[0092] ② Take a sample to test the dynamic viscosity of the polyamic acid slurry, and the test result is 77648cps; add 444.44g of 10% mass fraction NMP dispersion of nano aluminum nitride (average particle size 30nm) into the above polyamic acid slurry, and stir it for 3h to make the nano aluminum nitride evenly dispersed in the polyamic acid slurry;
[0093] ③ The viscosity of the polyamic acid slurry was sampled and tested to be 63541 cps. The polyamic acid slurry with qualified viscosity was transferred to a storage tank for wet spinning. According to the 1500 dtex linear density specification, it was extruded at a spinning speed of 20 m / min through spinning metering. The polyamic acid underwent a dehydration and ring-closing reaction at a temperature of 500°C to obtain a finished polyimide composite fiber.
[0094] Example 6
[0095] A polyimide composite fiber, the preparation of which comprises the following steps:
[0096] ① Circulating water at a temperature of 45°C was introduced into the jacket of a 50L reactor into which nitrogen was continuously introduced to preheat the reactor; after the reactor was preheated, 40kg of NMP solvent was added into the reactor and heated in a water bath; a NMP sample was taken from the reactor using a vial for moisture test, and the test result was 139.660ppm; 1922.37g of diamine monomer R3 was weighed and all of it was put into the NMP solvent at one time, and it was continuously stirred in a warm water bath for 3h until it was evenly dispersed; the warm water in the jacket of the reactor was discharged, and cooling water at a temperature of 5°C was filled in to cool the solution in which the diamine monomer had been evenly dispersed to 5°C; 2522.07g of dianhydride monomer BPDA was added to the cooled solution in the reactor; stirring was continued for 12h, and the dianhydride monomer and the diamine monomer were polymerized to form a polyamic acid slurry;
[0097] ② Take a sample to test the dynamic viscosity of the polyamic acid slurry, and the test result is 69813cps; add 444.44g of 10% mass fraction NMP dispersion of nano aluminum nitride (average particle size 30nm) into the above polyamic acid slurry, and stir it for 3h to make the nano aluminum nitride evenly dispersed in the polyamic acid slurry;
[0098] ③ The viscosity of the polyamic acid slurry sampled and tested was 60112cps. The polyamic acid slurry with qualified viscosity was transferred to a storage tank for wet spinning. According to the 1500dtex linear density specification, the slurry was extruded at a spinning speed of 20m / min through spinning metering. The polyamic acid underwent a dehydration ring-closing reaction at a temperature of 500°C to obtain a finished polyimide composite fiber.
[0099] Example 7
[0100] A polyimide composite fiber, the preparation of which comprises the following steps:
[0101] 1. Preparation of NMP dispersion of MWCNTs:
[0102] Under nitrogen protection, 444.44 g of solvent NMP was added to a three-necked flask. While stirring, 44.44 g of carboxylated multi-walled carbon nanotube (MWCNTs) powder was slowly added. Ultrasonic oscillation was continued at 60 W for 3 h to make the dispersion system uniform, and an NMP dispersion of MWCNTs was obtained for later use.
[0103] 2. Preparation of polyimide composite fibers:
[0104] ① Circulating water at a temperature of 45°C was introduced into the jacket of a 50L reactor into which nitrogen was continuously introduced to preheat the reactor; after the reactor was preheated, 40kg of NMP solvent was added into the reactor and heated in a water bath; a NMP sample was taken from the reactor using a vial for moisture test, and the test result was 128.531ppm; 1527.29g of diamine monomer R3 and 245.59g of diamine monomer p-PDA were weighed and all were put into the NMP solvent at one time, and stirred continuously in a warm water bath for 3h until uniformly dispersed; the warm water in the jacket of the reactor was discharged, and cooling water at a temperature of 5°C was filled in, and the solution with uniformly dispersed diamine monomers was cooled to 5°C; 2671.66g of dianhydride monomer BPDA was added to the cooled solution in the reactor; stirring was continued for 12h, and the dianhydride monomer and the diamine monomer were polymerized to form a polyamic acid slurry;
[0105] ② Take a sample to test the dynamic viscosity of the polyamic acid slurry, and the test result is 88439cps; add the MWCNTs solution prepared in 1 into the above polyamic acid slurry, and stir it for 3h to make the MWCNTs dispersed evenly in the polyamic acid slurry;
[0106] ③ The viscosity of the polyamic acid slurry sampled and tested was 71325cps. The polyamic acid slurry with qualified viscosity was transferred to a storage tank for wet spinning. According to the 1500dtex linear density specification, the slurry was extruded at a spinning speed of 20m / min through spinning metering. The polyamic acid underwent a dehydration ring-closing reaction at a temperature of 500°C to obtain a finished polyimide composite fiber.
[0107] Comparative Example 1
[0108] A polyimide fiber, the preparation of which comprises the following steps:
[0109] ① Circulating water at a temperature of 45°C was introduced into the jacket of a 50L reactor into which nitrogen was continuously introduced to preheat the reactor; after the reactor was preheated, 40kg of NMP solvent was added into the reactor and heated in a water bath; a NMP sample was taken from the reactor using a vial for moisture test, and the test result was 128.531ppm; 1527.29g of diamine monomer R3 and 245.59g of diamine monomer p-PDA were weighed and all were put into the NMP solvent at one time, and stirred continuously in a warm water bath for 3h until uniformly dispersed; the warm water in the jacket of the reactor was discharged, and cooling water at a temperature of 5°C was filled in to cool the solution in which the diamine monomer had been uniformly dispersed to 5°C; 2671.66g of dianhydride monomer BPDA was added to the cooled solution in the reactor; stirring was continued for 12h, and the dianhydride monomer and the diamine monomer were polymerized to form a polyamic acid slurry;
[0110] ② The dynamic viscosity of the polyamic acid slurry was tested by sampling, and the test result was 113649 cps; the polyamic acid slurry with qualified viscosity was transferred to a storage tank for wet spinning operation; according to the 1500 dtex linear density specification, the spinning speed was 20 m / min through spinning metering extrusion, and the polyamic acid underwent a dehydration ring-closing reaction at a temperature of 500°C to obtain a finished polyimide fiber.
[0111] Comparative Example 2
[0112] A polyimide fiber, the preparation of which comprises the following steps:
[0113] ① Circulating water at a temperature of 45°C was introduced into the jacket of a 50L reactor into which nitrogen was continuously introduced to preheat the reactor; after the reactor was preheated, 40kg of NMP solvent was added into the reactor and heated in a water bath; a NMP sample was taken from the reactor using a vial for moisture test, and the test result was 128.531ppm; 1861.34g of diamine monomer ODA was weighed and all of it was put into the NMP solvent at one time, and it was continuously stirred in a warm water bath for 1h until it was evenly dispersed; the warm water in the jacket of the reactor was discharged, and cooling water at a temperature of 5°C was filled in to cool the solution in which the diamine monomer had been evenly dispersed to 5°C; 2027.55g of dianhydride monomer PMDA was added to the cooled solution in the reactor; stirring was continued for 12h, and the dianhydride monomer and the diamine monomer were polymerized to form a polyamic acid slurry;
[0114] ② The dynamic viscosity of the polyamic acid slurry was tested by sampling, and the test result was 113649 cps; the polyamic acid slurry with qualified viscosity was transferred to a storage tank for wet spinning operation; according to the 1500 dtex linear density specification, the spinning speed was 20 m / min through spinning metering extrusion, and the polyamic acid underwent a dehydration ring-closing reaction at a temperature of 500°C to obtain a finished polyimide fiber.
[0115] In order to verify the progress of the embodiments of the present application, the following performance tests were performed on the polyimide composite fiber prepared in the above embodiments and the polyimide fiber prepared in the comparative example:
[0116] 1. Dynamic viscosity test: Take out about 50mL of polyamic acid slurry with a sampling bottle and use a rotational viscometer to test the viscosity of the slurry. The test steps are as follows: adjust the rotational viscometer to a horizontal position, select the 4# rotor, set the speed to 6RPM, and place the rotor vertically into the slurry to perform the viscosity test;
[0117] 2. Tensile strength test: Test and collect data in accordance with GB / T 14344-2022 "Test method for tensile properties of chemical fiber filaments";
[0118] 3. Thermal conductivity test: Test and collect data in accordance with GB / T 42919.4-2023 "Determination of thermal conductivity and thermal diffusivity of plastics Part 4: Laser flash method";
[0119] The above test results are shown in Table 1 below:
[0120] Table 1
[0121]
[0122] From the above test results, it can be seen that the thermal conductivity K of the polyimide composite fiber prepared in the embodiment of the present application is greater than 0.93W / (m·K), and the tensile strength is greater than 25cN / dtex, so that the polyimide composite fiber has high tensile strength and high thermal conductivity.
[0123] In comparative example 1, since no high-heat nanomaterials were added, the thermal conductivity was only 0.59 W / (m·K). However, in examples 1 to 7 of the present application, after adding thermally conductive nanomaterials, the thermal conductivity of the polyimide composite fiber was increased to not less than 0.93 W / (m·K).
[0124] The polyimide fiber of the "dianhydride monomer PMDA + diamine monomer ODA" system in Comparative Example 2 lacks hydrogen bonds between polymer chains and does not add any high-heat nanomaterials, so its tensile strength is significantly different from that of the polyimide composite fiber of the "dianhydride monomer BPDA + diamine monomer R3 + diamine monomer p-PDA + high-heat nanomaterial" system or "dianhydride monomer BPDA + diamine monomer R3 + high-heat nanomaterial" provided in Examples 1 to 7 of the present application. And since no high-heat nanomaterials are added in Comparative Example 2, its thermal conductivity is significantly lower than that of the polyimide composite fiber after adding nanomaterials in Examples 1 to 7 of the present application.
[0125] The embodiments of the present application achieve a high tensile strength of more than 25 cN / dtex for polyimide composite fibers through the system of "dianhydride monomer + diamine monomer + high-heat nanomaterial" or "multiple dianhydride monomers + diamine monomer + high-heat nanomaterial". At the same time, by mixing high thermal conductivity nanomaterials, the high-strength polyimide composite fibers have high thermal conductivity, which not only improves the tensile strength of the polyimide composite fibers, but also improves the thermal conductivity of the polyimide composite fibers, further expanding their application range, which is of great significance to the field of high-performance polyimide composite fibers.
[0126] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a polyimide composite material, characterized in that: The following steps are involved: Prepare polyamic acid slurry by using diamine monomer, dianhydride monomer and organic solvent; After the polyamic acid slurry and the nanomaterial are made into a mixed slurry, a spinning imidization treatment is performed to obtain a polyimide composite material; wherein the nanomaterial includes at least one of nano silicon carbide, aluminum nitride, carbon nanotubes, graphene, and nano silicon dioxide.
2. The method for preparing the polyimide composite material according to claim 1, characterized in that: The diamine monomer includes at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminobenzanilide, 2-(4-aminophenyl)-5-aminobenzimidazole, and 2-(4-aminophenyl)-5-aminobenzoxazole; And / or, the dianhydride monomer includes at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, and bisphenol A diether dianhydride; And / or, the organic solvent includes at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, γ-butyrolactone, and cyclohexanone; and / or, the molar ratio of the diamine monomer to the dianhydride monomer is (0.95-1.05):1; And / or, the mass of the nano material is 0.1% to 2% of the total mass of the diamine monomer and the dianhydride monomer; And / or, in the nanomaterial, the particle size D50 of the particles is 10nm to 50nm; and / or, the carbon nanotubes are selected from silsesquioxane-grafted multi-walled carbon nanotubes; And / or, the graphene is selected from multilayer graphene oxide.
3. The method for preparing the polyimide composite material according to claim 2, characterized in that: The diamine monomers include at least two of 4,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminobenzanilide, 2-(4-aminophenyl)-5-aminobenzimidazole, and 2-(4-aminophenyl)-5-aminobenzoxazole; And / or, the preparation step of the polyamic acid slurry comprises: dissolving the diamine monomer in the organic solvent under an inert atmosphere at a temperature of 40° C. to 50° C., cooling to 0° C. to 5° C., and then adding the dianhydride monomer for mixing; And / or, the viscosity of the polyamic acid slurry is 30000cps to 300000cps; And / or, the spinning imidization treatment step includes: the mixed slurry is extruded through spinning metering at a spinning speed of 15 m / min to 25 m / min according to a linear density specification of 1000 dtex to 2000 dtex, and the polyamic acid undergoes a dehydration ring-closing reaction at a temperature of 400°C to 600°C to obtain a polyimide composite fiber.
4. The method for preparing the polyimide composite material according to claim 2 or 3, characterized in that: The nanomaterial comprises the silsesquioxane-grafted multi-walled carbon nanotubes. The preparation of the silsesquioxane-grafted multi-walled carbon nanotubes comprises the following steps: under an inert atmosphere, dispersing the carboxylated multi-walled carbon nanotubes in a thionyl chloride solvent, and subjecting the solvent to reflux treatment to obtain acyl chloride multi-walled carbon nanotubes; dispersing the acyl chloride multi-walled carbon nanotubes, triethylamine and aminated silsesquioxane in chloroform for mixed reaction, and separating and purifying the reaction products to obtain the silsesquioxane-grafted multi-walled carbon nanotubes.
5. The method for preparing the polyimide composite material according to claim 4, characterized in that: The mass ratio of the chlorinated multi-walled carbon nanotubes, the triethylamine and the amino silsesquioxane is 1:(0.8-1.2):(1.8-2.5); And / or, the temperature of the mixed reaction is 60° C. to 70° C., and the treatment time is 12 to 36 hours.
6. A polyimide composite material, characterized in that: The polyimide composite material comprises polyimide and nanomaterials, wherein the nanomaterials comprise at least one of nano silicon carbide, aluminum nitride, carbon nanotubes, graphene, and nano silicon dioxide.
7. The polyimide composite material according to claim 6, characterized in that: In the nanomaterial, the particle size D50 of the particles is 10nm to 50nm; and / or, the carbon nanotubes are selected from silsesquioxane-grafted multi-walled carbon nanotubes; And / or, the graphene is selected from multilayer graphene oxide; And / or, in the polyimide composite material, the mass percentage of the nano material is 0.1% to 2%.
8. The polyimide composite material according to claim 6 or 7, characterized in that: The polyimide composite material is a polyimide composite fiber; And / or, the thermal conductivity of the polyimide composite material is not less than 0.93 W / (m·K); And / or, the tensile strength of the polyimide composite material is not less than 25 cN / dtex.
9. The polyimide composite material according to claim 8, characterized in that: And / or, the diameter of the polyimide composite fiber is 5 μm to 15 μm; And / or, the linear density of the polyimide composite fiber is 1000 dtex to 2000 dtex.
10. An application of a polyimide composite material, characterized in that: The polyimide composite material prepared by the method according to any one of claims 1 to 5, or the polyimide composite material according to any one of claims 6 to 9 is applied to at least one field of aerospace, electronics industry, automobile industry, protective products, and shipbuilding.
Citation Information
Cited By
Bionic multilevel structure high-fatigue-resistance stretchable flexible substrate material and controllable preparation method thereof
CN120842582A
Secondary foaming polyimide heat insulation composite material and preparation method thereof
CN121270915A
Preparation method of regenerated aramid composite fiber
CN121556170A
A method for preparing regenerated aramid composite fibers
CN121556170B